Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.491
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Hierarchy into Text Encoder: a Contrastive Learning Approach for Hierarchical Text Classification

Abstract: Hierarchical text classification is a challenging subtask of multi-label classification due to its complex label hierarchy. Existing methods encode text and label hierarchy separately and mix their representations for classification, where the hierarchy remains unchanged for all input text. Instead of modeling them separately, in this work, we propose Hierarchyguided Contrastive Learning (HGCLR) to directly embed the hierarchy into a text encoder. During training, HGCLR constructs positive samples for input te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…In it, categories are treated in isolation (i.e., as having no relationship between one another) [15,16]. In contrast, HTC deals with documents whose labels are organized in structures that resemble a tree or a directed acyclic graph (DAG) [91,92]. In these structures, each node contains a label to be assigned, such as in Figure 6.…”
Section: Types Of Hierarchical Classificationmentioning
confidence: 99%
“…In it, categories are treated in isolation (i.e., as having no relationship between one another) [15,16]. In contrast, HTC deals with documents whose labels are organized in structures that resemble a tree or a directed acyclic graph (DAG) [91,92]. In these structures, each node contains a label to be assigned, such as in Figure 6.…”
Section: Types Of Hierarchical Classificationmentioning
confidence: 99%
“…For example, "tumor" was converted to "An H&E image of tumor". As a natural comparison on the zero-shot task, we compared PLIP with the original CLIP model, which has been frequently used for other medical image tasks [31][32][33] and has already been trained from other medical images. Our analysis showed that PLIP consistently outperformed the baseline CLIP model and the results from predicting the majority class (or Majority) (Figure 2c).…”
Section: Plip Can Perform Zero-shot Classification On New Datamentioning
confidence: 99%
“…This approach uses the relationships between labels in the hierarchy to regularize the model and prevent overfitting. Furthermore, as the hierarchical multi-label classification task corresponds to the relationships among labels stored in the hierarchy, an increasing number of studies are considering not only the information provided by the classification target but also the corresponding representation of the hierarchical structure of labels [ 25 , 26 ]. These methods assign varying weights to distinct parts of the content representation that are the most associated with each label in the hierarchy, taking into account the interdependence between the representation of the hierarchical structure and the classification target.…”
Section: Related Workmentioning
confidence: 99%